Educational Leadership and Management - SHANAZ, DR. RUBINA (The journal of contemporary issues in business and government, 2021)
The area of education management and leadership is pluralist, with many conflicting views and the resulting lack of consensus on the specific disciplinary existence. Educational leadership is of great importance in early part of the 21st Century because of the common perception that leadership efficiency is the school and student outcomes are significantly different. Additionally, there is growing awareness that schools need successful leaders and administrators to provide their learners with the education they should be. Schools required committed and trained teachers but in turn they need highly effective leadership & support from different senior and middle managers. Although the required for successful leader is generally recognized, there is far less assurance about which leaderships practices are more likely to deliver desirable outcomes. Paper explore the theoretical staining for the fields of management and educational leadership, analyze various leaderships model, & address the proof of their comparative efficacy in creating productive schools.